Concentrated growth and spatial disparities in Korea - Kwan-Ryul Lee; Dong-Ho Shin (European Regional Science Association (ERSA), 2015)
The purpose of this study is to analyze the conditions and change of spatial inequality of South Korea according to the spatial policy. For this, this study will characteristics of the spatial policies by Korean government for 20 years (1995~2014), and will analyze what effect the spatial policy had on the spatial inequality of South Korea. South Koreas spatial inequality is very severe in the world. For example, concentration of Seoul, Korea is much higher than London, England, Tokyo, Japan and Paris, France. Therefore, South Koreas top priority for sustainable development is to solve concentration to capital region and spatial inequality. However, South Korea has pushed forward alternately the growth policy and balance policy for 20 years. Spatial policy of South Korea had been carried forward by the growth policy till 1998, but it changed to the balance policy between 1998~2007. Since 2008, it has been being pushed forward by the growth policy again. As a result, spatial inequality of South Korea somewhat eased off between 2000~2005, but it rather has shown a tendency of being expanded since. Particularly, the spatial inequality is broadening in population, economic, industry, finance and the powers sectors. In addition, infrastructure, health and welfare, education sectors, whose spatial inequality is relatively low, the spatial inequality is being expanded.
Keywords: R5; 330; Spatial Policy; Spatial Inequality; South Korea